2006
DOI: 10.4304/jcm.1.4.48-57
|View full text |Cite
|
Sign up to set email alerts
|

LITeTag: Design and Implementation of an RFID System for IT-based Port Logistics

Abstract: <p class="MsoNormal" style="text-align: left; margin: 0cm 0cm 0pt; layout-grid-mode: char;" align="left"><span class="text"><span style="font-family: ">Logistics has grown dramatically, especially where identifying, locating, or tracking objects in ports are important, because ports are gateways to extended markets. In this paper, we analyze the new requirements of port logistics after a brief introduction and present a system prototype. Then we describe the design and implementation of an RF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Some studies on active RFID systems complying with ISO/IEC 18000-7 have recently been reported [9,10]. These developed active RFID tags and readers that are in accordance with the standard, but they did not deal with tag collection performance with a large number of tags.…”
Section: Previous Workmentioning
confidence: 96%
“…Some studies on active RFID systems complying with ISO/IEC 18000-7 have recently been reported [9,10]. These developed active RFID tags and readers that are in accordance with the standard, but they did not deal with tag collection performance with a large number of tags.…”
Section: Previous Workmentioning
confidence: 96%
“…Production dispatching automation [38][39][40] Application of emerging information technologies at ports such as the Internet of Things and cloud computing [39,41,42] Emergency response capabilities [38,41] Port Logistics Supply Chain System…”
Section: Port Production and Operation Systemsmentioning
confidence: 99%
“…These systems use tagged objects (shopping carts in our case) and the well-known triangulation technique to establish the location of objects. Real-time locator systems have been recently installed in several industries, e.g., hospitals (Sokol, 2005), and ports (Cho et al, 2006).…”
Section: Ability To Track Shopping Cartsmentioning
confidence: 99%